Learning Effectiveness on Santri Learning Achievement at Riyadlul Muta'alimin Islamic Boarding School Cikaramat - Rima Erviana; Kun Nurachadijat (P3M IAI Nusantara Batang Hari, 2023)
This research is motivated by the consistency of Islamic boarding school residents in applying religious learning in collaboration with general learning. This study aims to determine the effectiveness of learning on student achievement at the Riyadlul Muta'alimin Islamic Boarding School in Cikaramat, Sukabumi Regency using indicators of learning effectiveness and learning achievement indicators that are expected to achieve this goal. This research is a descriptive qualitative research with research subjects being Islamic boarding school students at the wustha level. The object of this study is the effectiveness of learning as an independent variable on student achievement as the dependent variable. This study used data collection techniques in the form of observation, interviews and documentation, which were obtained through mini-research and literature studies. Data analysis with data reduction, data presentation and conclusion. The validity of the data using triangulation of sources and techniques. The results showed that the effectiveness of learning affects the achievement of students, by fulfilling the indicators of learning effectiveness, namely indicators of management and implementation of learning (students can take part in learning by combining two curricula, namely the cottage curriculum and the government curriculum), communicative teaching and learning process (students can express opinions or ask questions to ustadz), active response of students (senior students can actively guide or practice learning to junior students), ustadz motivation through learning innovation (shown by not only learning lecture or bandongan methods but by studying outside or honing students' skills), and learning outcomes ( indicated by 90% of students being able to meet the KKM score and being able to win the championship). According to the author, all of that can be created with discipline in managing time to study and meet daily needs.